(untitled) (Global Journal of Medical Research, 2015)
The incidence and pattern of suicide vary from country to country. Cut throat injuries can beeither suicidal or homicidal. These are well recognized methods of homicide and are less commonly used in suicides and are very rarely accidental. Suicide by incising one’s own throatis always associated with hesitation marks and homicidal wounds are not associated with one. Psychiatric illness, psychological stress and poverty are some of the associatedfactors of suicidal cut throat injury. when a patient comes with suicidal cut throat injuries, a multidisciplinary approach is required in the effective management of victims. This requires the close collaboration of the Otorhinolaryngologist, the anaesthesiologist and the psychiatrist.